How to improve performance and prevent burnout in safety representatives - Dal Corso, Laura; Carluccio, Francesca; Scarcella, Malì; Bartolucci, Giovanni Battista; Bizzotto, Rosana; Vianello, Liviano; Magosso, Doriano; De Carlo, Nicola Alberto (La Medicina del Lavoro, 2019)
Background: The present work is part of a greater research project, aimed to examine Safety Representatives’ (SRs) role, twenty years after the appointment of this figure. Objectives: The study aims to investigate the role of some personal and organizational dimensions in the promotion of SRs’ well-being, in terms of reducing burnout and improving performance. Methods: The study involved 455 SRs operating in North East Italy. They completed a self-report questionnaire, regarding conflicts with co-workers, ethical conflict, training satisfaction, work engagement, performance, and burnout. Results: Structural equation models show that work engagement partially mediates (γ=-0.52, p<0.001; β=0.23, p<0.01) the relationship between conflict with co-workers and performance (γ=-0.26; p<0.01), as well as partially mediating (γ=0.14, p<0.05; β=0.23; p<0.01) the relationship between training satisfaction and performance (γ=0.21, p<0.001). Moreover, it totally mediates the relationship between conflict with co-workers and burnout (γ=-0.52, p<0.001; β=-0.40, p<0.001), as well as totally mediating the relationship between training satisfaction and burnout (γ=0.14, p<0.05; β=-0.40, p<0.001). Finally, ethical conflict is positively associated with burnout (γ=0.047, p<0.001). Conclusions: This study provides useful information about the improvement of SRs’ well-being, highlighting the importance of their involvement in this role.